Barriers and facilitators to implementing status-neutral HIV care in an urban jail system - Socrates, Brindet; LeClair, Amy M.; Jaffe, Kaitlyn; Evans, Linnea; Batchelder, Abigail W.; Moner, Emily; Daudelin, Denise; Irie, Whitney; Ngassa, Yvane; Morales, Yoelkys; Levison, Julie; Evans, Elizabeth A.; Wurcel, Alysse G. (Tufts University Tisch Library, 2026)
Keywords: HIV, PrEP, Carceral healthcare, Qualitative, Implementation; Springer Open.